Adaptive Primary Literature: Disciplinary Literacy in a Science Classroom - Pidgeon, Mackenzie (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
Literacy is a fundamental part of a student’s success and within the science classroom. Yet science teachers do not take the time to teach content area literacy. Disciplinary literacy (DL) offers a meaningful way for science teachers to teach literacy instruction without sacrificing content instruction. One form of disciplinary literacy that is useful is Adaptive Primary Literature (APL). Textbooks in science classrooms often portray scientific phenomenon as absolute fact, without providing evidence to support the claims. This portrayal of information leads to a gap in the language of science used by professionals and the language of school science. Adaptive Primary Literature helps bridge the gap between the two. This paper reviews the need for DL and APL in science classrooms.